IbDM Bagi Penguatan Kelompok Sadar Wisata dalam Destination Branding Desa Wisata di Kabupaten Bantul - Oktiva Anggraini (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community service activities aimed at strengthening the institutional village tourism in branding tourist destinations. The pre-service survey at the beginning of the series of activities founded that at the location of the partner villages: the skills and education of the group and the management of tourism awareness were minimal; lack of awareness of the location's residents of the importance of developing sustainable protected forest areas; partners who are still minimal to participate in developing tourist destinations and the low cost of Bantul regency for special tourism promotion. Another challenge was that ecotourism development requires creativity and innovation, cooperation and promotion as well as good coordination and marketing. Regional-based tourism development spurred the involvement of regional and local community elements. Community service activities aimed to improve the ability of partners in managing the potential of ecotourism, especially related to the branding of tourist destinations, which increases the income of partners. The approach taken in the action program are 1) the Rural Appraisal Participatory Model (PRA); 2) Entrepreneurship Capacity Building (ECB) Model. The implementation of community service programs received a good response from partners shown by the presence and participation during the IT assessment and training took place, the Partner realized the importance of efforts to strengthen partner institutions so as to develop tourism business networks efficiently and optimally, becoming more resilient amid competition for similar tourism products. Partners increasingly realized the importance of branding in the tourism industry as an easy way for consumers to identify, build perceptions and values, set quality and standards that are easily managed, increase demand for local products that will indirectly impact the economy of surrounding communities and increase economies of scale.Keywords: institutional strengthening, branding, tourist destinations; network, ecotourism, tourism.